2021
DOI: 10.1080/13621718.2021.1923441
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of electrically assisted stationary shoulder friction stir welded Ti6Al4V

Abstract: The effect of modifying microstructure and texture by electric current on mechanical properties of electrically assisted stationary shoulder friction stir welded Ti6Al4V alloy were investigated. The width of the 'bowl-shaped' stir zone gradually increased with the increasing current value and texture of the joints changed abruptly with an increasing current from 0 to 300 A. The macrozones consisting of similar orientated grains in the heat-affected zone have the highest deformation degree and the lowest hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Figure 5 shows that measured peak temperatures at different distances from the welding centre line was verified by the CFD model and predicted peak temperature was almost the same as experimentally measured peak temperature (with an error of less than 5%), which proved the accuracy of numerical simulation. Our previous studies indicated that α / β lamellar laths precipitated at prior β grains boundary in the surface and centre of all the SZs [10], with a peak temperature exceeding the β transus temperature, whereas peak temperature in SZ bottom composed of the bimodal structure was below the β transus temperature. These results are in accordance with our simulation results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows that measured peak temperatures at different distances from the welding centre line was verified by the CFD model and predicted peak temperature was almost the same as experimentally measured peak temperature (with an error of less than 5%), which proved the accuracy of numerical simulation. Our previous studies indicated that α / β lamellar laths precipitated at prior β grains boundary in the surface and centre of all the SZs [10], with a peak temperature exceeding the β transus temperature, whereas peak temperature in SZ bottom composed of the bimodal structure was below the β transus temperature. These results are in accordance with our simulation results.…”
Section: Resultsmentioning
confidence: 99%
“…However, defects readily occurred in titanium alloys fabricated by conventionally fusion welding [4,5], such as porosity, low ductility, high residual stress and large deformation [6][7][8]. The conventional friction stir welding (FSW) of titanium alloys [9] has good weld quality and low residual stress, but large difference occurred in heat generation and material flow between the shoulder and pin owing to its low thermal conductivity [10]. Therefore, stationary shoulder stir friction welding (SSFSW) was developed by The Welding Institute, UK, to eliminate the problem of uneven temperature distribution along the thickness direction.…”
Section: Introductionmentioning
confidence: 99%
“…FSW, facilitated by the Joule effect, may aid in reducing root malformations caused by a deficiency of penetration as well as decreasing the hardness of the heat-affected zone (HAZ). Bai et al [9] demonstrate increment in tensile strength (TS) of welded joints and percentage elongation to fracture by delivering current in their investigation on Electric Assisted FSW (EAFSW) of Ti6Al4V. When the current was raised from 0A to 300A, the tensile strength improved by 16.5 percent.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that welding parameters are the dominant factors affecting the quality of the dissimilar FSW joints. Optimised welding parameters (including rotation rate and traverse speed) can be obtained through experiments to produce high quality joints [15][16][17]. It was also found that the relative position of raw materials in respect with the welding direction, often referred as the advancing side (AS) or retreating side (RS), can play a critical role in the FSW process.…”
Section: Introductionmentioning
confidence: 99%